L'utilisation des emprises de lignes de transport d'énergie électrique par l'orignal ( Alces alces ) en hiver - Joyal, Robert; Lamothe, Pierre; Fournier, Robert (Canadian Journal of Zoology, 1984)
The influence of electric transmission rights-of-way on the activity of moose (Alces alces) was determined by aerial surveys during winter and inventories of browsed plant species the following summer. Moose make significant less use of the rights-of-way than the adjacent forest, but the edge zone is frequented more. Winter grounds are also found significantly less frequently in these transmission corridors. The difference in use between the two habitats is even more pronounced when the rights-of-way have been treated with a phytocide. The quantity of browse in untreated rights-of-way does not differ significantly from that found in the adjacent forest, but in treated corridors, it is three times lower. Rights-of-way that are 90 m wide are more frequently crossed in winter than those that are 140 m wide. Wild red cherry (Prunus pensylvanica) is the most browsed species in southern parts of the corridors, whereas white birch (Betula papyrifera) is the preferred plant of moose in northern areas. There is no difference between the types of forest stands in adjacent forest stations that are used by moose and those that are not. The influence of the electric transmission rights-of-way is considered weak because the natural density of the moose population is low.[Journal translation]